Effect of Small Group Discussion Method Learning on Concept Understanding of Senior High School Students - Syairah, Anisa (Journal of Mathematics Science and Computer Education, 2024)
This study was motivated by limited comprehension of mathematical concepts among students in mathematics. One potential solution is implementing the small group discussion learning method. The objective of this study is to ascertain the efficacy of the acquisition of small-group discussion methods in mathematics subjects on students' comprehension of mathematical concepts. This form of research is a quasi-experiment with a non-equivalent control group design. The samples in this study were class , which consisted of 27 students as the experimental class, and , which consisted of 28 students as the control class, selected using Simple Random Sampling. The t-test results indicated a substantial difference in the comprehension of mathematical concepts between the experimental and control class students. Consequently, H0 was rejected, and H1 was accepted. It can be concluded that the small group discussion method is more effective than conventional learning in enhancing students' comprehension of mathematical concepts. The small group discussion method effectively enhances students' comprehension of concepts by involving them directly in the learning process. The small group discussion method has the potential to enhance students' comprehension of concepts, as demonstrated by the empirical findings of this study. Thus, this study suggests that this method is an effective teacher learning strategy.